Can Islamic Work Ethics and Ethical Climate Reduce Counterproductive Work Behavior? - Hayati, Keumala; Yuningsih, Yuningsih; Caniago, Indra (FEB - Universitas Lampung, 2018)
This study examines the effect of Islamic Work Ethic (IWE) and Ethical Climate (EC) on Counterproductive Work Behavior (CWB). The sample was 115 employees of Islamic financial institutions in Lampung, Indonesia. The analysis shows that IWE has a negative effect on CWB, EC also has a negative effect on CWB. This finding shows that CWB can be reduced by IWE and EC. EC influence is slightly higher than IWE shows that although IWE plays a good role in reducing CWB, the role of the ethical climate in the organization has slightly greater in reducing CWB.